A case study of document readiness in the Administration and Management Working Group on accreditation results at Lalolae Health Center - Sartini Risky; Lodes hadju; Sri Mulyani; Azlimin; Muhammad Rachmat (Elsevier, 2021)
Objective: The results of the self-assessment assessment at the Lalolae Public Health Center which was the target of the 2017-2019 accreditation assessment in East Kolaka Regency showed that most of the low scores were in the administration and management group. This study aims to determine the relations between the readiness of accreditation documents in the Administration and Management Working Group on the accreditation results of the Lalolae Public Health Center in East Kolaka Regency. Methods: This type of research is quantitative using a cross sectional design. The number of samples in this study were all people in charge of the administrative and management working group at the Lalolae Public Health Center who were determined by the purposive sampling method. This research was carried out from May 1 to July 20, 2020 and took place at the Lalolae Health Center. The sample in this study is 30 respondents. Results: There are 3 documents in chapter I that have unfulfilled categories, there are 4 documents in chapter ii that have unfulfilled categories, and there are 4 documents in chapter III that have unfulfilled categories. Conclusion: There is a relation between the readiness of accreditation documents in the administration and management groups to the results of accreditation of Public Health Center.